Exploring the Structural, Electronic, and Magnetic Properties of MoTe2 and MoSe2 Materials Via DFT+U Approach - Pokharel, Arpan; Khanal, Kamal; Yadav, Sukrit Kumar; Neupane, Tejendra; Paudel, Ganesh; Rijal, Om Shree; Neupane, Hari Krishna (Journal of Nepal Chemical Society, 2025)
Two-dimensional (2D) transition metal dichalcogenides (TMDCs) materials have potential applications in the fields of electronic and optoelectronic devices. In the present work, we have studied the structural, electronic, magnetic, and dynamical properties of MoSe2 and MoTe2 (3×3) supercell monolayer structures using the density functional theory (DFT) method with the PBE+U functional, employing the quantum ESPRESSO computational package. The structural properties of the considered materials are studied by the analysis their estimated ground state energy and bond length between nearest-neighbors atoms present in the structures. MoSe2 and MoTe2 materials are found to be structurally stable, having hexagonal structures. To predict the electronic and magnetic properties of the materials, we have interpreted their band structure, density of states (DoS), and partial density of states (PDoS) plots. From the discussion, it is found that MoTe2 and MoSe2 have small band gap and non-magnetic properties. Hence, they are classified as small band gap semiconducting, non-magnetic materials. Moreover, we have developed the phonon dispersion curves to predict dynamical stability of the materials. It is found that all the frequencies at each symmetric points of the considered materials have positive values. This implies that they are dynamically stable materials. Hence, based on the analysis of the electronic, magnetic and dynamical properties of MoTe2 and MoSe2 materials, they can be used in the fields of electronic and optoelectronic device applications.